Thesis Writing for Master's and Ph.D. Program (Springer Singapore, 2018)
This book on Thesis Writing for Master's and Ph.D. program focuses on the difficulties students encounter with regard to choosing a guide; selecting an appropriate research title considering the available resources; conducting research; and ways to overcome the hardships they face while researching, writing and preparing their dissertation for submission. Thesis writing is an essential skill that medical and other postgraduates are expected to learn during their academic career as a mandatory partial requirement in order to receive the Master's degree. However, at the majority of medical schools, writing a thesis is largely based on self-learning, which adds to the burden on students due to the tremendous amount of time spent learning the writing skills in addition to their exhausting clinical and academic work. Due to the difficulties faced during the early grooming years and lack of adequate guidance, acquiring writing skills continues to be a daunting task for most students. This book addresses these difficulties and deficiencies and provides comprehensive guidance, from selecting the research title to publishing in a scientific journal.